(untitled) (Journal of Pakistan Orthopaedic Association, 2020)
Objective: To determine the radiological and functional outcome of Ilizarov ring fixator in the management of infected nonunion of long bones of the lower limb. Methods: This descriptive study was conducted in Mercy Teaching Hospital Peshawar from 3rd January 2011 to 23rd June 2019. All patients of infected non-union of tibia and femur meeting the inclusion criteria were treated with Ilizarov ring fixator. Post-surgery outcomes were analyzed in terms of bone and functional results as per “Association for the Study and Application of Methods of Ilizarov (ASAMI) Scoring System”. Results: A total of 40 cases including 37(92.5%) males and 3(7.5%) females with the mean age 33.325± 9.4 years (range 3 to 60 years) were included in our study. In 30(75%) cases tibia and in 10(25%) cases femur was involved. Bone defect after radical debridement was 2-centimeter(cm) or less in 25(62.5%) cases and they were treated with monofocal compression distraction technique using Ilizarov ring fixator. In 15(37.5%) cases bone loss after radical debridement was more than 2cm with mean defect 7.06 cm (ranging from 4cm to 12 cm) and they were treated with bone segment transport. Post-operative outcome as assessed with ASAMI scoring system showed excellent radiological result in 35 (87.5%) patients and good in 5 (12.5%) cases. Excellent functional results were noted 30 (75%) cases, good in 9 (22.5%) and fair in 1 (2.5%) case No poor radiological or functional results were reported. Conclusion: The Ilizarov ring fixator produced excellent and good radiological and functional results in majority of our patients with infected nonunion of long bones of the lower limb. We therefore recommend that Ilizarov should be the first treatment modality to treat infected non unions of tibia and femur.